2021
DOI: 10.3340/jkns.2020.0315
|View full text |Cite
|
Sign up to set email alerts
|

Long Time Efficacy and Safety of Microvascular Decompression Combined with Internal Neurolysis for Recurrent Trigeminal Neuralgia

Abstract: Objective : To explore the clinical efficacy and safety of microvascular decompression (MVD) combined with internal neurolysis (IN) in the treatment of recurrent trigeminal neuralgia (TN) after MVD. Methods : Sixty-four patients with recurrent TN admitted to the hospital from January 2014 to December 2017 were divided into two groups according to the surgical method. Twenty-nine patients, admitted from January 2014 to December 2015, were treated with MVD alone, whereas 35 admitted from January 2016 to Decemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Alternatively, if there is no vascular compression upon any part of the trigeminus, TN is usually classi ed as [8][9][10], and internal neurolysis (IN) surgery is usually performed with satisfactory treatment e cacy. Internal neurolysis (IN) involves longitudinal incision of the intracranial nerve root to achieve nerve micro destruction and is highly effective at curing ITN and signi cantly reducing the incidence of facial sensory disorders and the degree of numbness [11,12]; therefore, IN has been gradually accepted by an increasing number of scholars [13][14][15]. Our research team also used IN to treat ITN and came to similar conclusions [16].…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Alternatively, if there is no vascular compression upon any part of the trigeminus, TN is usually classi ed as [8][9][10], and internal neurolysis (IN) surgery is usually performed with satisfactory treatment e cacy. Internal neurolysis (IN) involves longitudinal incision of the intracranial nerve root to achieve nerve micro destruction and is highly effective at curing ITN and signi cantly reducing the incidence of facial sensory disorders and the degree of numbness [11,12]; therefore, IN has been gradually accepted by an increasing number of scholars [13][14][15]. Our research team also used IN to treat ITN and came to similar conclusions [16].…”
Section: Introductionmentioning
confidence: 81%
“…Therefore, surgical procedures are often performed without any reference but rather according to the doctor's experience, which may lead to ineffective or unnecessary iatrogenic damage after surgery. In fact, single vascular decompression surgery is usually ineffective, and to avoid the need for a second operation due to ineffective decompression and to improve the success rate of the rst operation, IN surgery alone [13] or combined with vascular decompression [15] is often used in clinical treatment. This is clearly due to a lack of helplessness, and more precise methods need to be further developed.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Also about 90% of patients suffered from facial numbness after MVD combined with internal neurolysis. [19][20][21] Complications could also impact the life quality of the patients. Zhang et al compared the effect and complications of redo MVD and percutaneous radiofrequency thermocoagulation for TN with failed MVD, the result showed that re-do MVD had better pain control and less complication.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of hypaesthesia, however, is markedly higher in series from centers which use mechanical intraoperative measures to alter sensory function of the trigeminal nerve either routinely or in patients in whom no clear cause for recurrent TN has been detected [43]. Such measures include "combing" or "pinching" of the trigeminal nerve or "internal neurolysis," as well as "partial transection of the trigeminal nerve," "partial nerve section," or "partial sensory rhizotomy" [1,10,11,17,30,43,49]. Especially when using more extensive sectioning procedures, facial numbness may occur in more than 50% of patients after posterior fossa re-exploration [1,31].…”
Section: Discussionmentioning
confidence: 99%